Residential Altitude Associates With Endurance but Not Muscle Power in Young Swiss Men - Gassmann, Norina N.; Matthes, Katarina L.; Eppenberger, Patrick; Brabec, Marek; Panczak, Radoslav; Zwahlen, Marcel; Bender, Nicole; Wyss, Thomas; Rühli, Frank J.; Staub, Kaspar (Frontiers in Physiology, 2020)
Introduction: Physical fitness benefits health. However, there is a research gap on how physical fitness, particularly aerobic endurance capacity and muscle power, is influenced by residential altitude, blood parameters, weight, and other cofactors in a population living at low to moderate altitudes (300-2100masl). Materials and Methods: We explored how endurance and muscle power performance changes with residential altitude, Body Mass Index (BMI), hemoglobin and creatinine levels among 108,677 Swiss men aged 18-22 years (covering >90% of Swiss birth cohorts) conscripted to the Swiss Armed Forces between 2007-2012. The test battery included a blood test of about 65%, a physical evaluation of about 85%, and the BMI of all conscripts. Results: Residential altitude was significantly associated with endurance (p <0.001) but not with muscle power performance (p = 0.858) after adjusting for all available cofactors. Higher BMI showed the greatest negative association with both endurance and muscle power performance. For muscle power performance, the association with creatinine levels was significant. Elevated C-reactive protein and hemoglobin levels were stronger contributors in explaining endurance than muscle power performance. Conclusion: We found a significant association between low to moderate residential altitude and aerobic endurance capacity even after adjustment for hemoglobin, creatinine, BMI and sociodemographic factors. Non-assessed factors such as vitamin D levels, air pollution, and lifestyle aspects may explain the presented remaining association partially and could also be associated with residential altitude. Monitoring the health and fitness of young people and their determinants is important and of practical concern for disease prevention and public health implications.